Brote de pseudotuberculosis en ratones BALB/C y reproduccion experimental de la enfermedad - Nuñez, J.F.=700 1 Merino, N.; Quintana, M.
(Es, En)
Ilus., 17 ref.
Keywords: ENFERMEDADES INFECCIOSAS; CORYNEBACTERIUM PSEUDOTUBERCULOSIS; INOCULACION; RATON; REPRODUCCION; CUBA